2022
DOI: 10.1177/08902070221080954
|View full text |Cite
|
Sign up to set email alerts
|

The role of interpersonal perceptions of social inclusion and personality in momentary self-esteem and self-esteem reactivity

Abstract: Empirical research has demonstrated that self-esteem is significantly shaped by social interactions and perceptions of social inclusion; however, less is known about individual differences in the reactivity of momentary self-esteem to social inclusion. Zooming into social interactions, we used data from two adolescent samples (overall N > 200) in two different social settings (i.e., a standardized laboratory interaction vs. real-life interactions) to examine the associations between different interpersonal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 93 publications
1
11
0
Order By: Relevance
“…Specifically, the experience of positive social encounters in daily life was related to more positive evaluations of the self in that moment. Extending previous research (Bleckmann et al, 2023; Denissen et al, 2008; Hutteman et al, 2015), this reactivity effect generalized across the two different age groups in our sample, that is, late adolescence and late adulthood. At the same time, it should be noted that the subsample of older adults was comparably small.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Specifically, the experience of positive social encounters in daily life was related to more positive evaluations of the self in that moment. Extending previous research (Bleckmann et al, 2023; Denissen et al, 2008; Hutteman et al, 2015), this reactivity effect generalized across the two different age groups in our sample, that is, late adolescence and late adulthood. At the same time, it should be noted that the subsample of older adults was comparably small.…”
Section: Discussionsupporting
confidence: 86%
“…Along the lines of previous ESM studies using this sample (Bleckmann et al, 2023;Wieczorek et al, 2022), we included a number of control variables. First, following the recommendations by Bolger and Laurenceau (2013), we coded a variable indicating the starting date and timeline of the ESM for the 7 days (coded 0-6).…”
Section: Esm Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Individual self-esteem can be divided into two levels, internal and external. The internal level is mainly expressed in the members’ desire to be a strong, competent and confident individual in OKCs; the external level refers to the individual’s desire to gain the respect, trust and praise of others in OKCs, and thus achieve a higher social status ( Bleckmann et al, 2022 ). According to the Network Working Group perspective, an OKC is a task-and goal-oriented virtual community whose members tend to gain a sense of task accomplishment based on task contributions ( Pierce and Gardner, 2004 ).…”
Section: Research Model and Hypothesesmentioning
confidence: 99%
“…1Research has shown that the relationship between self-esteem and the social environment (i.e., social interactions and relationships) is bidirectional (Harris & Orth, 2020): a person’s self-esteem affects their social experiences (de Moor et al, 2021; Harris & Orth, 2020), and positive social experiences can increase a person’s self-esteem (Bleckmann et al, 2022, 2023; Denissen et al, 2008; Hutteman et al, 2015). In the present research, we focus on the former by examining the link between trait self-esteem and meta-liking within social interactions.…”
mentioning
confidence: 99%